The information support of statistical study of secondary education in Ukraine - Ганюкова, А.Ю. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
In article is devoted to the sources information formation support of statistical studying of functioning of secondary education inUkrainewhich is base for adoption of scientifically reasonable administrative decisions in social policy. Indirect sources of information, including monitoring’s and researches of the international and regional organizations are also considered. The main shortcomings are defined and the possible directions of improvement of modern information support are proved.